The final days - Woodward, Bob 1943-; Bernstein, Carl 1944- (Simon and Schuster, 1994)
The Final Days is the classic, behind-the-scenes account of Richard Nixon's dramatic last months as president. Moment by moment, Bernstein and Woodward portray the taut, post-Watergate White House as Nixon, his family, his staff, and many members of Congress strained desperately to prevent his inevitable resignation. This brilliant book reveals the ordeal of Nixon's fall from office -- one of the gravest crises in presidential history.